DFNB16 is a frequent cause of congenital hearing impairment: implementation of STRC mutation analysis in routine diagnostics. (21st January 2014) - Vona, B.; Hofrichter, M.A.H.; Neuner, C.; Schröder, J.; Gehrig, A.; Hennermann, J.B.; Kraus, F.; Shehata‐Dieler, W.; Klopocki, E.; Nanda, I.; Haaf, T.
Abstract Increasing attention has been directed toward assessing mutational fallout of stereocilin (STRC), the gene underlying DFNB16. A major challenge is due to a closely linked pseudogene with 99.6% coding sequence identity. In 94 GJB2/GJB6‐mutation negative individuals with non‐syndromic sensorineural hearing loss (NSHL), we identified two homozygous and six heterozygous deletions, encompassing the STRC region by microarray and/or quantitative polymerase chain reaction (qPCR) analysis. To detect smaller mutations, we developed a Sanger sequencing method for pseudogene exclusion. Three heterozygous deletion carriers exhibited hemizygous mutations predicted as negatively impacting the protein. In 30 NSHL individuals without deletion, we detected one with compound heterozygous and two with heterozygous pathogenic mutations. Of 36 total patients undergoing STRC sequencing, two showed the c.3893A>G variant in conjunction with a heterozygous deletion or mutation and three exhibited the variant in a heterozygous state. Although this variant affects a highly conserved amino acid and is predicted as deleterious, comparable minor allele frequencies (MAFs) (around 10%) in NSHL individuals and controls and homozygous variant carriers without NSHL argue against its pathogenicity. Collectively, six (6%) of 94 NSHL individuals were diagnosed with homozygous or compound heterozygous mutations causing DFNB16 and five (5%) as heterozygous mutation carriers. Besides GJB2/GJB6 (DFNB1), STRC is a major contributor to congenital hearing impairment.